Regular Exercise May Restore Certain Age-Related Alterations of Adaptive Immunity and Rebalance Immune Regulation - Papp, Gábor; Szabó, Krisztina; Jámbor, Ilona; Mile, Marianna; Berki, Alexandra Réka; Arany, Attila Csaba; Makra, Gabriella; Szodoray, Peter; Csiki, Zoltán; Balogh, László (Frontiers in Immunology, 2021)
Age-related changes of the immune system lead to an increased morbidity and mortality due to enhanced vulnerability to infectious diseases and malignancies. Recent studies revealed the important effects of physical activity on immune functions, which may largely depend on the type of exercise, its intensity and duration. However, limited information is available regarding the immunological effects of sport activities in older ages. The aim of our study was to examine the changes in a wide spectrum of lymphocyte subtypes after regular workout among healthy elderly individuals. We enrolled 29 elderly women with sedentary lifestyle (mean age: 67.03 ± 3.74 years) to take part in a 6-week long functional conditioning gymnastic exercise program. The percentages of peripheral natural killer (NK), NKT cells, T and B lymphocyte subtypes (early-/late-activated T, naïve and memory T, cytotoxic T (Tc), T-helper (Th)1, Th2, Th17, T regulatory type 1 (Tr1), CD4+CD127lo/-CD25bright Treg, as well as naïve and memory B cells) were determined by flow cytometry. Evaluation of the changes in functional capability of Treg cells was based on in vitro functional assays. At the end of exercise program, in parallel with improvements in body composition and physical performance, significant changes in naïve and memory lymphocyte ratios were observed. Importantly, levels of naïve Tc cells elevated, ratios of effector memory Tc cells decreased and distribution of memory B cells rearranged as well. Additionally, proportions of late-activated HLA-DR+ T cells increased, while percentages of anti-inflammatory interleukin (IL)-10 producing Tr1 cells, as well as immunosuppressive CD4+CD127lo/-CD25bright Treg cells decreased following the exercise workout. Changes observed after the regular exercise program indicate an improvement in the age-related redistribution of certain naïve and memory cell proportions and a retuned immune regulation in older ages.